2015
DOI: 10.1027/1864-9335/a000230
|View full text |Cite
|
Sign up to set email alerts
|

Heritage Identity and Maintenance Enhance Well-Being of Turkish-Bulgarian and Turkish-German Adolescents

Abstract: This study compares Turkish minority youth in Bulgaria and Germany by examining differences in ethnic identity (heritage and mainstream), acculturation (host culture adoption and heritage culture maintenance), and their influence on psychological and sociocultural outcomes. Participants were 178 Turkish-Bulgarian and 166 Turkish-German youth (mean age of 15.96 years). Youth in both cultural contexts regarded their Turkish identity and culture maintenance as more relevant than their mainstream identity and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…The findings were consistent with expectations and provided support for previous studies (Dimitrova et al, 2012(Dimitrova et al, , 2014(Dimitrova et al, , 2015(Dimitrova et al, , 2016. The collective identity functioned as an assembled latent factor predicting well-being in both groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings were consistent with expectations and provided support for previous studies (Dimitrova et al, 2012(Dimitrova et al, , 2014(Dimitrova et al, , 2015(Dimitrova et al, , 2016. The collective identity functioned as an assembled latent factor predicting well-being in both groups.…”
Section: Discussionsupporting
confidence: 92%
“…The present study follows the argumentation adopted in previous studies in which a single latent variable of collective identity with positive loadings for ethnic, familial, and religious identities was positively associated with well-being (Dimitrova et al, 2012(Dimitrova et al, , 2014(Dimitrova et al, , 2015(Dimitrova et al, , 2016. These core domains were chosen because, in the literature, minority members have shown to exhibit stronger ethnic, familial and religious identities (Lopez et al, 2011) and because these aspects are considered to increase feelings of coherence, positive self-evaluation, and belongingness in proximal social groups and, in turn, well-being.…”
Section: Ethnic Familial and Religious Components Of Collective Idenmentioning
confidence: 76%
See 1 more Smart Citation
“…First, we expect Turkish-Bulgarian youth to endorse their Turkish identity more strongly than their Bulgarian identity (Hypothesis 1c). This expectation is based on prior work highlighting the relevance of Turkish domains of identity and acculturation in Turkish ethnic minority groups in Europe (e.g., Germany and the Netherlands) as well as Bulgaria Dimitrova, Aydinli, Chasiotis, Bender, & van de Vijver, 2015;Dimitrova, Chasiotis, Bender, & van de Vijver, 2014a, 2014b. These studies generally show that across all these cultural contexts, Turkish groups regarded maintenance of their Turkish culture as more important than that of the host culture (e.g., Bulgarian, German, and Dutch) adoption.…”
Section: Aims Context and Hypothesesmentioning
confidence: 98%
“…This scale adopted the same format as the ethnic identity scale and has been previously applied in research with ethnic minority groups in Eastern Europe (Dimitrova et al, 2013a(Dimitrova et al, , 2013bDimitrova et al, 2015). Examples of the 21 items are "I see problems of my family as my problems" and (Dimitrova et al, 2013a(Dimitrova et al, , 2013bDimitrova et al, 2015) is a 21-item scale that again adopted the previously reported format of ethnic and familial identity scales. Sample items were "Being part of my religious community has much to do with how I feel about myself" and "When I need help, I can count on my religious community" (α = .89 to .96).…”
Section: Participants and Proceduresmentioning
confidence: 99%